2014
DOI: 10.1002/uog.13243
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of neurosonography and MRI in clinical management of fetuses referred with central nervous system abnormalities

Abstract: Objective To assess the accuracy of expert neurosonography (two-and three-dimensional NSG)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
89
5
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(100 citation statements)
references
References 9 publications
(19 reference statements)
4
89
5
2
Order By: Relevance
“…In conclusion, we think that if the indication for MRI is correct, the clinical relevance of this additional examination is in the range of 5-10%, as pointed out by Drs Malinger and Lerman-Sagie in their letter and their study 3,5 and by ourselves 4 . However, the real point of this letter is to underscore that, as far as fetal CNS anomalies are concerned, the diagnostic path should be from the screening setting to neurosonography and, only if the neurosonologist deems it appropriate, to MRI, with a defined diagnostic query for the neuroradiologist.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…In conclusion, we think that if the indication for MRI is correct, the clinical relevance of this additional examination is in the range of 5-10%, as pointed out by Drs Malinger and Lerman-Sagie in their letter and their study 3,5 and by ourselves 4 . However, the real point of this letter is to underscore that, as far as fetal CNS anomalies are concerned, the diagnostic path should be from the screening setting to neurosonography and, only if the neurosonologist deems it appropriate, to MRI, with a defined diagnostic query for the neuroradiologist.…”
mentioning
confidence: 71%
“…The first regards our own broad experience, reported in this Journal, probably after Drs Prefumo and Rossi performed their literature search, because it represents one of the largest series of fetuses examined with neurosonography and, in selected cases, MRI 4 . In this study, we found that: 1) MRI was deemed necessary to characterize the neurosonographic diagnosis in only 16.3% (126/773) of the cases; 2) clinically relevant findings were evident on MRI in only 7.9% (10/126) of cases, and only if performed in the third trimester; 3) large masses/cysts and, to a lesser extent, posterior fossa anomalies, are the category of CNS anomalies for which MRI may add clinically relevant information, doing so in 42.9% (3/7) and 24.8% (3/26) of cases, respectively.…”
mentioning
confidence: 99%
“…Both methods were concordant in 86.5% of the cases with respect to the final diagnoses. Noteworthy, NSG was more effective when performed < 24 weeks of gestation (93.1% vs. 90.4%) [15]. Summing up, neurosonographic multidimensional evaluation is an accurate, first-level diagnostic modality in prenatal detection of CNS malformations.…”
Section: Transvaginal Neuroimagingmentioning
confidence: 97%
“…Summing up, neurosonographic multidimensional evaluation is an accurate, first-level diagnostic modality in prenatal detection of CNS malformations. In the event of an unclear diagnosis, MRI performed > 24 weeks of gestation may provide additional data in about 5-10% of the cases [15,16].…”
Section: Transvaginal Neuroimagingmentioning
confidence: 99%
“…Therefore, factors that exert its action upon CNS during the third trimester will interact with the fetal neuronal development; also other pathological conditions such as hemorrhage, thrombosis, or calcifications can occur in late gestation [12]. Consequently a normal 20 weeks ultrasound scan does not guarantee a normal CNS development, so it is mandatory to reassess the brain structures in the third trimester [13,14].…”
Section: Screening Normal Aspectsmentioning
confidence: 99%